Quantitative fMRI using hyperoxia calibration: reproducibility during a cognitive Stroop task. - Goodwin, J; Vidyasagar, R; Balanos, G; Bulte, D; Parkes, L (2009)
Arterial spin labelling allows simultaneous measurement of both the blood-oxygenation-level-dependent (BOLD) and the cerebral blood flow (CBF) response to changes in neural activity. The addition of a hypercapnia or hyperoxia calibration allows additional quantification of changes in the cerebral metabolic rate of oxygen (CMRO(2)). In this study we test the reproducibility of measurements derived using the hyperoxia approach, during a cognitive Stroop task. A QUIPSSII sequence is used at 3 T to collect simultaneous CBF and BOLD signal during two 3 min periods of hyperoxia and an 8 min Stroop task. Hyperoxia was administered via an open system and end-tidal values were sampled via a nasal cannula; average end-tidal values of 60% were reached. This procedure is repeated to allow the reproducibility of the estimated parameters to be tested. The use of a cognitive Stroop task allows testing of the measurements in frontal and parietal regions as well as sensorimotor areas in which previous studies have been focussed. We find reduced reproducibility of the calculated parameters compared to the hypercapnia approach, thought to be attributable to lower absolute BOLD and CBF responses. In particular we do not find 'n' to have improved reproducibility compared to other parameters, as has been found in previous work using the hypercapnia approach. Across all brain areas we report a value of DeltaCMRO(2) of 12% and neurovascular coupling constant n of 2.5. Interestingly we find n to be higher in parietal and frontal areas in comparison to the primary motor cortex.